Pengaruh Partisipasi Dalam Mgmp Dan Motivasi Kerja Guru Terhadap Kompetensi Profesional Guru Pak Di Kabupaten Humbang Hasundutan Tahun 2025 - Lidia Pasaribu; Binur Panjaitan; Hisardo Sitorus (Journal of Innovative and Creativity, 2026)
The purpose of this study was to determine and analyze 1) the effect of participation in MGMP on the professional competence of PAK teachers in Humbang Hasundutan Regency in 2025; 2) the effect of teacher work motivation on the professional competence of PAK teachers in Humbang Hasundutan Regencyin 2025; and 3) the simultaneous effect of participation in MGMP and teacher work motivation on the professional competence of PAK teachers in Humbang Hasundutan Regency in 2025. The method used in this study is a quantitative research method. The population is all Christian Religious Education teachers who are members of MGMP PAK in Humbang Hasundutan Regency, totaling 55 teachers and sampling in this study using total sampling technique. The instrument trial was conducted on 30 PAK teachers in Samosir Regency so that it was known that all research instruments were declared valid and reliable because they had met the validity and reliability value criteria. Data were collected with a closed questionnaire of 75 items. The results of the data analysis show that: 1) the Fcount value > Ftable is 25.587 > 3.15, thus it is known that there is a positive and significant influence between participation in MGMP on the professional competence of PAK teachers in Humbang Hasundutan Regency in 2025. The influence is 32.6%, 2) the Fcount value > Ftable is 27.918 > 3.15, thus it is known that there is a positive and significant influence between teacher work motivation on the professional competence of PAK teachers in Humbang Hasundutan Regency in 2025. The influence is 34.5%, and 3) the Fcount value > Ftable is 19.733 > 3.15, thus it is known that there is a positive and significant influence simultaneously between participation in MGMP and teacher work motivation on the professional competence of PAK teachers in Humbang Hasundutan Regency in 2025. The influence is 43.1%, thus Ha is accepted and H0 is rejected.